A Graphene/Polycrystalline Silicon Photodiode and Its Integration in a Photodiode–Oxide–Semiconductor Field Effect Transistor - Yu-Yang Tsai; Chun-Yu Kuo; Bo-Chang Li; Po-Wen Chiu; Klaus Y. J. Hsu (Micromachines, 2020)
In recent years, the characteristics of the graphene/crystalline silicon junction have been frequently discussed in the literature, but study of the graphene/polycrystalline silicon junction and its potential applications is hardly found. The present work reports the observation of the electrical and optoelectronic characteristics of a graphene/polycrystalline silicon junction and explores one possible usage of the junction. The current–voltage curve of the junction was measured to show the typical exponential behavior that can be seen in a forward biased diode, and the photovoltage of the junction showed a logarithmic dependence on light intensity. A new phototransistor named the “photodiode–oxide–semiconductor field effect transistor (PDOSFET)” was further proposed and verified in this work. In the PDOSFET, a graphene/polycrystalline silicon photodiode was directly merged on top of the gate oxide of a conventional metal–oxide–semiconductor field effect transistor (MOSFET). The magnitude of the channel current of this phototransistor showed a logarithmic dependence on the illumination level. It is shown in this work that the PDOSFET facilitates a better pixel design in a complementary metal–oxide–semiconductor (CMOS) image sensor, especially beneficial for high dynamic range (HDR) image detection.